LIJPHART'S DEMOCRACY IDEA DAN TURKEY - TULGA, Ahmet Yi?italp (Faculty of Social and Political Science Universitas Brawijaya, 2019)
This paper tries to apply Lijphart?s way of description with ten factors for the two models of democracy to the Republic of Turkey. Turkey, with her important location, which is a country with a different political structure and social structure, can be added to Lijphart example. This research mainly analysis Turkish political system with Lijphart?s majoritarian and consensus democracy idea. In this study, while examining the case of Turkey, the World Bank, IMF, and IV project, Freedom House reports and data were used.